New Challenges In Teaching Spoken English For Employment At The Undergraduate Level (Journal of Namibian Studies : History Politics Culture, 2023)
The employment sector in India is diversifying with the liberalization of the economy. Education at the undergraduate level is however at present, not in tune with the requirements of the job market. In order to provide employment related skills to the undergraduate students, more stress needs to be placed on linking education with work. This is applicable to the teaching of Spoken English also.This paper addresses the need to give more importance to the development of the speaking skills in English, which is the most neglected skill among the language skills taught at the undergraduate level. The paper examines the following:• The notion of spoken English as it is taught in the undergraduate level.• The nature of spoken English taught through the existing English courses at the undergraduate level.• The scope of spoken English taught through the option vocation-oriented Functional English course4. The work-related skills that need to be linked with the teaching of spoken English at the undergraduate level Based on the observation: a three stage approach for co-ordinating the efforts to relate spoken English to employment needs is suggested.